Development of P2TB Surveillance Information System on Children In Health Office of Surabaya - Septiani, Neneng Dwi; Syahrul, Fariani; Suryaningdiah, Daniek; Yuliandari, Rosita Dwi (Health Notions, 2018)
The implementation of SIK in TB program uses Integrated TB Information System (SITT), which is an electronic web-based logging and reporting system and connected directly to SIK nationally. In practice, SIK P2TB in Health Office of Surabaya still needs development especially in analyzing some child TB indicators. The purpose of this research is to design the development of P2TB surveillance information system of children in Health Office of Surabaya to overcome the problem of current P2TB surveillance information system. The research used descriptive design which aims to describe the model of design development of tuberculosis surveillance information system of children in Health Office of Surabaya by indepth interview to 3 (three) managers of P2TB. Informants in this study as many as 3 people consisting of 2 TB vice supervisors and one contractor of P2TB. Data analysis was described in the form of DFD (Data Flow Diagram) and analyzed descriptively. the results of this study indicate that the type of information required on the output component is proportion of TB TB among all TB patients, case of TB case finding, success rate of TB treatment, coverage of children <5 years who received PP INH, and proportion of children who completed PP INH among all children receiving PP INH; The design of the components of the P2TB surveillance information system development process is the child TB analysis process and dissemination of the results of the analysis in accordance with the design of the DFD; and Data requirement on the input component is in accordance with the data in SITT 10.04 and recap PP INH. The development of surveillance information systems at P2TB is expected to assist in analyzing some of the child TB indicators that have not been processed so as to provide information for TB child reporting. Keywords: Child TB, Surveillance, Information